The Relationship Between Level Anxiety And Sleeping Quality Of Breast Cancer Patients In One Day Care Chemotherapy Room - Lucilla Suparmi; Fransisca Anjar Rina Setyani (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2021)
Objective: Chemotheraphy is one of theraphy managements for breast cancer patients. Chemotherapy has some side effects like nausea, gag, alpoesia, etc. Those can increase patients’ anxiety. Then, this anxiety will give impact on sleeping quality disoeder. This research aims to identify the anxiety level of breast cancer patients in chemotheraphy ODC room.Methods: This research used crossectional design. There are 32 respondents as research sample choosen by purposive sample technic.Results: The result shows that most repondents (68,75 %) didnot feel anxiety, 15,63% got mild anxiety, 9,38% got moderate and severe anxiety, and no one got panic anxiety. Most respondents (71,87) had good sleeping quality and 28,13% had poor sleeping quality. There is no relationship between level anxiety and sleeping quality of cancer patients with P value = 0,182.Conclusion: There is no relationship between level anxiety and sleeping quality of cancer patients. Nurse should do persoal approach to patients who are still having severe anxiety and poor sleeping qualitiy.